Preclinical Polymodal Hallucinations for 13 Years before Dementia with Lewy Bodies - Carlo Abbate; Pietro Davide Trimarchi; Silvia Inglese; Niccolò Viti; Alessandra Cantatore; Lisa De Agostini; Federico Pirri; Lorenza Marino; Renzo Bagarolo; Daniela Mari (Behavioural Neurology)
Objective. We describe a case of dementia with Lewy bodies (DLB) that presented long-lasting preclinical complex polymodal hallucinations. Background. Few studies have deeply investigated the characteristics of hallucinations in DLB, especially in the preclinical phase. Moreover, the clinical phenotype of mild cognitive impairment-(MCI-) DLB is poorly understood. Methods. The patient was followed for 4 years and a selective phenomenological and cognitive study was performed at the predementia stage. Results. The phenomenological study showed the presence of hypnagogic and hypnopompic hallucinations that allowed us to make a differential diagnosis between DLB and Charles Bonnet syndrome (CBS). The neuropsychological evaluation showed a multiple domain without amnesia MCI subtype with prefrontal dysexecutive, visuoperceptual, and visuospatial impairments and simultanagnosia, which has not previously been reported in MCI-DLB. Conclusions. This study extends the prognostic value of hallucinations for DLB to the preclinical phases. It supports and refines the MCI-DLB concept and identifies simultanagnosia as a possible early cognitive marker. Finally, it confirms an association between hallucinations and visuoperceptual impairments at an intermediate stage of the disease course and strongly supports the hypothesis that hallucinations in the earliest stages of DLB may reflect a narcolepsy-like REM-sleep disorder.